The Using of Legal Resource from Internet in the Legal Studies: Array - Sulaksono, Sulaksono; Efendi, Jonaedi (Acta Universitatis Danubius. Juridica, 2022)
This research is aimed to explain the using of Legal resource from Internet in the legal studies. This research is used the descriptive research using the legal resource which both finding the relevant analysis sources purposed to use in the research. Traditionally, the lawyer and law student finds the law principally in books housed in law libraries, so that lawyer and a law library are inseparable. Today lawyer and law student can be use online virtual library. Internet has expanded at a phenomenal rate, integrating various source of law into a vast interactive network. It use has already reshaped the conditions of legal research for many millions lawyer and law student around the world. Therefore understanding of the use of legal materials for legal research down load through virtual library, the rules and its academic ethics embodied is important even for the lawyer and law student.